The artistic censoring of sexuality : fantasy and judgment in the twentieth-century novel - Mooney, Susan (Ohio State University Press, 2008)
"In The Artistic Censoring of Sexuality: Fantasy and Judgment in the Twentieth Century Novel, Susan Mooney extensively examines four modernist and postmodernist novels that prompted in their day harsh external censorship because of their sexual content - Ulysses, Lolita, Time of Silence, and Russian Beauty. She shows how motifs of censorship, with all its restrictions, pressures, rules, judgments, and forms of negation, became artistically embedded in the novels' plots, characters, settings, tropes, and themes. These novels contest censorship's status quo and critically explore its processes and power. This study reveals the impact of censorship on literary creation, particularly in relation to the twentieth century's growing interest in sexuality and its discourses."--